2012
DOI: 10.1128/jvi.00483-12
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 Genetic Variants: Phylogeny and Classification Based on E6 and LCR

Abstract: Naturally occurring genetic variants of human papillomavirus type 16 (HPV16) are common and have previously been classified into 4 major lineages; European-Asian (EAS), including the sublineages European (EUR) and Asian (As), African 1 (AFR1), African 2 (AFR2), and North-American/Asian-American (NA/AA). We aimed to improve the classification of HPV16 variant lineages by using a large resource of HPV16-positive cervical samples collected from geographically diverse populations in studies on HPV and/or cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(185 citation statements)
references
References 29 publications
14
152
2
5
Order By: Relevance
“…Many authors have suggested that some lineages of HPV16 show greater associations with cervical neoplasms (Londesboroug et al, 1996;Bontkes et al, 1998;Zehbe et al, 1998;Villa et al, 2000;Xi et al, 2007;Schiffman et al, 2010;Smith et al, 2011;Cornet et al, 2012). This would partially explain why some HPV16 infections progress to HSIL or cancer, while others do not (Picconi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have suggested that some lineages of HPV16 show greater associations with cervical neoplasms (Londesboroug et al, 1996;Bontkes et al, 1998;Zehbe et al, 1998;Villa et al, 2000;Xi et al, 2007;Schiffman et al, 2010;Smith et al, 2011;Cornet et al, 2012). This would partially explain why some HPV16 infections progress to HSIL or cancer, while others do not (Picconi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…E6 and E7 are the major oncoproteins and are involved in tumorigenesis. LCR has been demonstrated to be the most variable region of HPV16 and contains the early promoter and regulatory elements involved in viral DNA replication and transcription (Cornet et al, 2012). Several authors have evaluated the association of specific HPV16 mutations with viral persistence and the development of cervical intraepithelial neoplastic lesions (Londesboroug et al, 1996: Bontkes et al, 1998Villa et al, 2000;Cornet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mpileup function from SAMtools (Li et al 2009) was used to detect SNPs and small INDELs in HPV genomes. HPV variants were classified by comparison of sequences to HPV16 lineage-specific SNPs as reported by the IARC HPV Variant Study Group (Cornet et al 2012).…”
Section: Whole-genome Sequencing and Analysismentioning
confidence: 99%
“…(Zhang and Tang, 2012) * HPV16 has been extensively sequenced to characterize subtypes and variants in a phylogenetic framework. According to geographic location and ethnic group, HPV16 variants have been classified into 4 lineages; 1) European-Asian (EAs) including the sublineage European (E, the prototype of HPV16) and Asian (As), 2) African 1 (AFR1), 3) African 2 (AFR2) and 4) North American/ Asian-American (NA/AA) including the sublineage North American, Asian-American 1 and Asian-American 2 (Yamada et al, 1997;Cornet et al, 2012). Epidemiological studies show an association between cervical cancer and HPV16 variants and report that HPV16 E6 variants may be more oncogenic than the prototype and thus carry a higher risk for development of invasive cervical disease (Xi et al, 2007;Schiffman et al, 2010;Gheit et al, 2011;Mosmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%